Viral Imagery: The Animated Face of Covid-19. (2nd July 2020) - Ehrlich, Nea
Abstract : Animated informational imagery about Covid-19 has become omnipresent; so too have imaginative depictions of how life has changed under lockdown, animating both the psychological and physical aspects of life in quarantine. This article examines the reasons why animation is an apt visual language to engage with Covid-19 and the wider epistemological and ethical issues that this raises about animated imagery in the digital era. I claim that animation has become so omnipresent in the visual culture of Covid-19 because of an interesting relation between (1) the definitions of animation; (2) animation's qualities as informational aesthetics; and (3) animation's central role in digital screen culture. As imagery that engages with a global epidemic, animation plays a dual role: as an increasingly dominant informational aesthetic in contemporary visual culture and as self-reflexive imagery about the nature of life.